101 American customs : Understanding American language and culture through common practices - Collis, Harry; Kohl, Joe (Lincolnwood Passport Books, 1999)
Introduction to American culture. American social life and customs. Provide an understanding of American language and culture through American words and actions in the workplace, places of worship, and recreation.
Keywords: Cơ bản